Evolution of Coffee Policies in Mexico. XIX-XXI Centuries - Oviedo-Rodríguez, Claudia (Revista de historia., 2024)
This paper characterizes the evolution of Mexican coffee policies, addressing how the state’s interest and its mechanisms for supporting coffee production have changed significantly over time. Three major phases of coffee policies were identified. First, during the late XIX and early XX centuries, the state was focused on expanding the number of hectares for coffee and facilitating land acquisition by large-scale farmers. Second, from 1958 to 1989, the state was interested in expanding coffee plantations and increasing productivity with higher-yield varieties and fertilizer. The state played a strong regulatory role in overseeing coffee prices and collecting farmers’ harvests; during this phase, small-scale farmers were the main target of support. Third, from 1989 to 2018, the state continued to promote increased productivity, but it also began to focus on improving quality. While small-scale farmers continued to be the principal target of support, the state significantly reduced its intervention in the coffee sector and primarily aided small-scale farmers through programs supplying plants and fertilizer.